Acute Kidney Injury in the Neonatal Period: Retrospective Data and Implications for Clinical Practice - Meidad Greenberg; Saray Sity-Harel; Sydney Benchetrit; Lewis Reisman; Tali Zitman-Gal; Daniel Erez; Maysam Shehab; Keren Cohen-Hagai (Children)
Background: Neonates, particularly those born prematurely or with low birth weight, face an elevated risk of developing Acute Kidney Injury (AKI) due to various factors. Perinatal and maternal considerations, often linked to preterm delivery, contribute to this heightened risk. Methods: A retrospective study of neonates admitted to the intensive care unit at a single Israeli Hospital who were diagnosed as having AKI. The study includes follow-up data on these children. Results: During the study period, 971 neonates were admitted to the Pediatric Intensive Care Unit (PICU), and 47 cases had a documented diagnosis of AKI. Thirty-four of them had available long-term data and were included in this analysis. A total of 13 out of 26 subjects with available blood pressure measurements had high blood pressure for their age percentile compatible with the definition of hypertension, and 6 out of 34 (17.6%) had proteinuria. Conclusions: These findings underscore the importance of increased clinical awareness and structured long-term follow-up for neonates who experience AKI.